Meningoencephalitis Disease Which Requires Optimal Approach in Emergency Manner - Pana, Marina (IntechOpen, 2017)
Meningoencephalitis remains a major global threat, despite the prevention, diagnosis, and antibiotic therapy that have been improved considerably in the last years. In this thematic issue, the scientists present their results of accomplished studies, in order to provide several guidelines regarding the strategies of diagnosis and treatment of patients with meningoencephalitis, by adding valuable data and thus helping public health decision.